Arroz más nutritivo contra la desnutrición en América Latina - Martínez Racines, César Pompilio; Borrero Correa, Jaime C.; Duque E., Myriam Cristina; Carabalí, Silvio J.; Silva, James; Tohme, Joseph M. (International Center for Tropical Agriculture, 2010)
More nutritive rice against malnutrition in Latin America Three topics are addressed briefly: (1) information available on the Fe and Zn contents of the grain of 11 rice cultivars; (2) factors affecting its contents; and (3) a plant breeding strategy proposed to increase the nutritional value of rice in Latin America. The data obtained are backed up by results obtained by the International Rice Research Institute (IRRI) and reveal significant differences among cultivars regarding rice grain Fe and Zn contents in both rough and polished rice. Acceptable Fe and Zn contents were also observed in several commercial varieties; these, however, were never selected to improve this aspect of nutritional quality. Recent scientific data indicate that plant breeding is an effective and reliable tool of reasonable cost to develop improved germplasm with a better nutritional value than current varieties. Research conducted by IRRI, within the framework of the HarvestPlus project, and by CIAT, through the AgroSalud project, indicates that genetic variability does exist in rice regarding grain Fe and Zn contents. In conclusion, it is considered feasible to improve the nutritional quality of rice in Latin America, and advances have been made in several areas.